Research on maximizing energy efficiency for relay-aided D2D communication - Xue WANG; Tao JIN; Zhihong QIAN; Liangshuai HU; Xin WANG (Tongxin xuebao)
In order to optimize the energy efficiency for relay-aided D2D communication underlaying cellular network,an algorithm was proposed while guaranteeing the quality of service of D2D users and cellular users.Firstly,the problem was formulated as a mixed integer nonlinear fractional programming problem,with the goal of maximizing the energy efficiency of all D2D users.Then,the maximizing energy efficiency problem was divided into three sub-problems,such as power allocation,relay selection and subcarrier assignment.Finally,the power allocation problem,the relay selection problem and the subcarrier assignment problem were addressed by Dinkelbach method and Lagrange multiplier method,Q-learning and Hungarian algorithm,respectively.The simulation results show that the proposed algorithm can improve the total energy efficiency of D2D users compared with existing algorithms.